2010
DOI: 10.1093/schbul/sbq087
|View full text |Cite
|
Sign up to set email alerts
|

Catatonic Schizophrenia: A Cohort Prospective Study

Abstract: Background: In the 20th century, catatonia was usually deemed a subtype of schizophrenia. Recently, the nature and classification of catatonia are being reconsidered. This study is the first to describe catatonia using prospectively collected data and to examine how catatonic schizophrenia differs from, or resembles, other types of schizophrenia. Methods: Data were analyzed in a cohort of 90 079 offspring followed from birth till ages 29-41 years. Proportional hazards models were used, calculating time to firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Due to these definition problems, the reported prevalence rates of catatonia in schizophrenia vary extensively (table 1). In a birth cohort study from Israel, 7.6% of the subjects who developed schizophrenia by the age of 35 years displayed the catatonic subtype [68]. The prevalence of catatonia appeared to decrease over the past century [69,70].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…Due to these definition problems, the reported prevalence rates of catatonia in schizophrenia vary extensively (table 1). In a birth cohort study from Israel, 7.6% of the subjects who developed schizophrenia by the age of 35 years displayed the catatonic subtype [68]. The prevalence of catatonia appeared to decrease over the past century [69,70].…”
Section: Clinical Perspectivesmentioning
confidence: 99%
“…The continued importance of identifying the presence of catatonia in these different contexts is supported by its familial aggregation and co-aggregation with schizophrenia and major mood disorders (Peralta and Cuesta, 2007), clear etiological attribution to a range of specific general medical conditions (Weder et al, 2008), and most importantly its relatively specific response to treatment with benzodiazepines and electroconvulsive therapy (Rohland et al, 1993;Hawkins et al, 1995;Bush et al, 1996;Caroff et al, 2007). Relative proportions of mood, primary psychotic, and neurological/medical disorders in samples of patients with catatonia vary across studies (Rosebush and Mazurek, 2010;Kleinhaus et al, 2012).…”
Section: Summary Of New Data and Limitations In Dsm-iv Treatment Of Cmentioning
confidence: 99%
“…This would also seem to counter the argument that delayed treatment caused catatonia. In another cohort study of 568 cases of catatonic patients, Kleinhaus and Harlap found an association with the schizophrenic diagnosis [30]. This may have been due to a selection bias in a sample with many psychotic patients.…”
Section: Prognosis/course Of Catatoniamentioning
confidence: 99%
“…Common theories to explain decreased prevalence of catatonia have included: use of increasingly-restrictive definitions of the syndrome; more reliable exclusion criteria; and improved treatment resulting in fewer cases reaching the catatonic stage associated with advanced illness [29,30,31,32,33]. Employment of alternative classification systems such as the Leonhard approach have yielded significantly more cases of catatonia than the use of RDC [21].…”
Section: Prognosis/course Of Catatoniamentioning
confidence: 99%
See 1 more Smart Citation